2017
DOI: 10.7309/jmtm.6.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Patient Navigator Facilitated Text Messaging Intervention Improves Linkage to care in Viral Hepatitis B: A Pilot Study

Abstract: Background: Despite the high prevalence of chronic hepatitis B (CHB) in Asian Americans and other ethnic groups, a majority of these populations remains unscreened and unprotected. A large percentage of those who are chronically infected with hepatitis B virus (HBV) are not linked to care owing to a poor health care access. The purpose of this study was to evaluate the use of mobile text messaging in engaging individuals with hepatitis B or at risk for it, and to assess their acceptance of text messaging inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The results of this study demonstrate that HepTalk can be employed to boost patient engagement and improve outcomes in hepatitis B care. This study further supports the finding of our previous study, which suggested that a form of mobile texting combined with the patient navigator program facilitated communication between the patients and HCPs and enhanced LTC [14]. HepTalk provided an effective communication mechanism through which patient navigators were able to guide participants to appropriate health care resources.…”
Section: Principal Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study demonstrate that HepTalk can be employed to boost patient engagement and improve outcomes in hepatitis B care. This study further supports the finding of our previous study, which suggested that a form of mobile texting combined with the patient navigator program facilitated communication between the patients and HCPs and enhanced LTC [14]. HepTalk provided an effective communication mechanism through which patient navigators were able to guide participants to appropriate health care resources.…”
Section: Principal Findingssupporting
confidence: 89%
“…However, it may be premature to consider these participants linked because some of these linked participants may not return to HCPs for follow-up in the future. Thus, although the texting intervention was significantly longer in this study compared with the intervention period employed in our previous study [14], studies with an intervention period greater than 6 months may be preferable to assess the sustainability of the efficacy of the HepTalk communication. This is particularly important because we have noted that a small but significant portion of CHB patients with long histories of infection saw HCPs once but did not sustain their LTC.…”
Section: Limitations Of This Studymentioning
confidence: 84%
See 1 more Smart Citation